Alien Intelligence Research Institute: a Perspective-Taking Activity for a Nuanced View on Traits and a Growth Mindset - Iglika V. Pavlova (Journal of Microbiology & Biology Education, 2022)
ABSTRACT Instructors can foster equitable learning environments when they communicate that they value growth and diversity and by providing opportunities for students to reflect and to engage in cross-group interactions with diverse others. Additionally, perspective-taking activities engage empathy and have been used to reduce racial bias. An activity was introduced at the start of the semester to promote a more scientifically informed view of traits and intelligence, while also encouraging creativity, evidence-based thinking, and teamwork in an introductory biology course that was taught in an online synchronous format due to the COVID pandemic. Student groups worked in breakout rooms to create a slide in a shared file describing a research plan to test for human intelligence from the perspective of an alien life form. Students had the freedom to choose their alien to have whatever abilities and intelligence they wanted. The activity was highly student-centered, with students showing through their work that an understanding of intelligence is closely linked to the methods used to measure it. In this way, the activity promoted a more nuanced understanding of traits. This COVID-era invention resulted in a successful strategy that can be used in a variety of course delivery formats to support the teaching of content, as well as to promote a growth learning mindset and inclusive education.